An Innovative Crop-Forage Intercrop System: Early Cycle Soybean Cultivars and Palisadegrass - Crusciol, Carlos Alexandre Costa [UNESP]; Mateus, G. P.; Nascente, A. S.; Martins, P. O. [UNESP]; Borghi, E.; Pariz, C. M. [UNESP] (Amer Soc Agronomy, 2012)
Agriculture and livestock integration is a sustainable practice that improves both crop yield and pasture recuperation/formation. However, to achieve success it is important to identify crop cultivars more adapted to intercropping with grasses. Therefore, the objective was to evaluate nutrient concentration and grain yield of soybean [Glycine max (L.) Merr.] cultivars with different life cycles as affected by palisadegrass [Brachiaria brizantha (Hochst. ex A. Rich) Stapf] intercropped in the same furrow at different depths, in a no-till system, as well as dry matter production and protein concentration of palisadegrass pasture. Experiments were performed during two growing seasons, on a Typic Haplorthox, at Botucatu, São Paulo State, Brazil. The experimental design was a randomized block, arranged in a 2 x 4 factorial scheme, with six replications. Treatments consisted of two cropping systems (sole cropped soybean; soybean and palisadegrass intercropped) and four soybean cultivars (super-early cycle [Monsoy 6101], early cycle [Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) 48], normal cycle [BRS 133], and late cycle [Emgopa 313]). Life cycle duration of the soybean had a marked effect, and only early cycle soybean were successful intercrops. Intercropping palisadegrass with super-early or early soybean cultivars were viable options to crop-livestock integration, because they did not affect both soybean or palisadegrass yield. In addition, with these cultivars, it was possible to cultivate grain and then afterward more time for cattle (Bos taurus and Bos indicus) grazing in the same area, providing greater revenue compared to sole soybean cropped or in the intercropping with longer cycle cultivars.